Prognostic Prediction of Acute Pyogenic Spondylitis That Resists Conservative Treatment - Murotani, Kazuhiro; Tamaki, Yasuyuki (Journal of Spine Research, 2023)
Introduction: This study aims to find the predictive factors of acute pyogenic spondylitis that resist conservative treatment.Methods: We studied 76 cases (men: 49 and women: 27, average age: 74 years, average follow-up period: 198 days) of acute pyogenic spondylitis where conservative treatment was followed. Subjects were compared by dividing into groups R of 30 and NR of 46 cases with and without resist of conservative treatment, respectively.Results: Average of age, men, periods from medical institution consultation to a diagnosis, the number of the infected vertebral bodies, compromised host, infection progress case of the MRI and resistant bacteria in groups R and NR were 76 and 72 years old, 20 and 29 cases, 7.4 and 8.3 days, 2 and 1.7 vertebral bodies, 20 and 23 cases, 9 and 14 cases, 7 and 8 cases, respectively. Notable differences were observed in the number of infected vertebral bodies. The average of body temperature at the first examination, 1 week, 2 weeks, 3 weeks, and 4 weeks after treatment, were 38.5°C and 38.6°C, 37.3°C and 37.2°C, 36.9°C and 37.0°C, and 37.0°C and 36.9°C, and 36.9°C and 36.8°C, respectively. The average of WBC at the first examination, 1 week, 2 weeks, 3 weeks, and 4 weeks after treatment were 10,847 and 13,776, 8,253 and 9,254, 8,011 and 7,533, 6,370 and 6,460, and 6,642 and 6,639 μL, respectively. Notable difference was observed in the WBC of the first examination. Average of CRP at the first examination, 1 week, 2 weeks, 3 weeks, and 4 weeks after treatment were 15.0 and 15.7, 8.6 and 6.4, 5.4 and 3.0, 5.4 and 2.9, and 4.8 and 1.9 mg/dl, respectively. Notable differences were observed among the CRP of 1 week, 2 weeks, 3 weeks, and 4 weeks after treatment. Using the multiplex logistic-regression analysis, only CRP of 4 weeks was notably different and the cutoff level was CRP = 2.0 mg/dl.Conclusions: Acute pyogenic spondylitis that resists conservative treatment was predictable using CRP of 4 weeks after treatment and the cutoff level was CRP = 2.0 mg/dl.